High molecular mass fraction in clinical isolates of Paracoccidioides brasiliensis Fração de alta massa molecular em isolados clínicos de Paracoccidioides brasiliensis - Andréa Longoni Fredrich; Luciene Airy Nagashima; Wander Rogério Pavanelli; Audrey de Souza Marquez; Mari Sumigawa Kaminami; Nilson de Jesus Carlos; Ayako Sano; Mario Augusto Ono; Eiko Nakagawa Itano (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Different serum levels of the IgG/IgE for Paracoccidioides brasiliensis high mass molecular (hMM) fraction (~366kDa) in the acute and chronic forms of the disease have been reported. Considering the nonexistence of hMM fraction investigation involving clinical isolates of P. brasiliensis, the present study aimed to investigate the presence of the hMM fraction (~366kDa) in cell free antigens (CFA) from P. brasiliensis clinical isolates. METHODS: CFA from 10 clinical isolates and a reference strain (Pb18) were submitted to SDS-polyacrylamide gel electrophoresis (SDS-PAGE) followed by gel image capturing and densitometer analysis. Additionally, CFA from 20 isolates and Pb18 were analyzed by capture ELISA (cELISA) using polyclonal (polAb) or monoclonal (mAb) antibodies to the hMM fraction. RESULTS: The presence of the hMM component was observed in CFA of all samples analyzed by SDS-PAGE/densitometry and by cELISA. In addition, Pearson's correlation test demonstrated stronger coefficients between hMM fraction levels using pAb and mAb (R = 0.853) in cELISA. CONCLUSIONS: The soluble hMM fraction was present in all the P. brasiliensis clinical isolates analyzed and the reference strain Pb18, which could be used as a source of this antigen. The work also introduces for first time, the cELISA method for P. brasiliensis hMM fraction detection. Analysis also suggests that detection is viable using polAb or mAb and this methodology may be useful for future investigation of the soluble hMM fraction (~366kDa) in sera from PCM patients. INTRODUÇÃO: Diferentes níveis sorológicos de IgG/IgE contra a fração de alta massa molecular (hMM) (~366kDa) de Paracoccidioides brasiliensis têm sido encontrados na PCM aguda e crônica. Considerando a inexistência de investigação sobre esta fração em isolados clínicos de P. brasiliensis, o objetivo deste estudo foi investigar a presença da fração hMM (~366kDa) no preparado livre de células (CFA) de P. brasiliensis obtidos de isolados clínicos. MÉTODOS: CFA de 10 isolados e de cepa ...